Evidence of exhausted lymphocytes after the third anti-SARS-CoV-2 vaccine dose in cancer patients - Benitez Fuentes, Javier David; Mohamed Mohamed, Kauzar; de Luna Aguilar, Alicia; Jiménez García, Carlos; Guevara-Hoyer, Kissy; Fernandez-Arquero, Miguel; Rodríguez de la Peña, M Antonia; Garciía Bravo, Laura; Jiménez Ortega, Alejandro Francisco; Flores Navarro, Paloma; Bartolome Arcilla, Jorge; Alonso Arenilla, Bárbara; et al. (Frontiers in Oncology, 2022)
Evidence is scant regarding the long-term humoral and cellular responses triggered by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mRNA vaccines in cancer patients after repeated booster doses. The possibility of T-cell exhaustion following these booster doses in this population has not yet been fully studied and remains uncertain. In this single-center prospective observational study, we explored the specific humoral and cellular response to S1 antigen in 36 patients with solid malignancies at baseline, and after the second and third doses of the mRNA-1273 vaccine. A dual behavior was observed: 24 (66.7%) patients showed partial specific IFN-γ response after the second dose that was further enhanced after the third dose; and 11 (30.5%) already showed an optimal response after the second dose and experienced a marked fall-off of specific IFN-γ production after the third (4 patients negativization), which might suggest T cell exhaustion due to repetitive priming to the same antigen. One (2.8%) patient had persistently negative responses after all three doses. Seroconversion occurred in all patients after the second dose. We then studied circulating exhausted CD8+ T-cells in 4 patients from each of the two response patterns, those with increase and those with decrease in cellular response after the third booster. The patients with decreased cellular response after the booster had a higher expression of PD1+CD8+ and CD57+PD1+CD8+ exhausted T cells compared with those with an increased cellular response both in vivo and in vitro. The proportion of PD1+CD8+ and CD57+PD1+CD8+ exhausted T cells inversely correlated with IFN-γ production. Our preliminary data show that the two-dose SARS-CoV-2 vaccine regimen was beneficial in all cancer patients of our study. An additional booster seems to be beneficial in suboptimal vaccine seroconverters, in contrast to maximal responders that might develop exhaustion. Our data should be interpreted with caution given the small sample size and highlight the urgent need to validate our results in other independent and larger cohorts. Altogether, our data support the relevance of immunological functional studies to personalize preventive and treatment decisions in cancer patients.